2019
DOI: 10.3846/jbem.2019.10448
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Mobile Applications for Identifying Tourism Destinations by Travellers: An Integrative Approach

Abstract: The purpose of the study is to provide an assessment of both how consumers adopt mobile tourism apps and how consumers use those apps to orient customer intentions to visit tourism destinations. The technology acceptance model (TAM) is used to explore customer intentions to adopt tourism apps. A survey of 630 tourism respondents found that the e-servicescape environment and e-word-of-mouth communication play major roles in determining intentions to adopt tourism apps and to visit tourism destinations. Perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…The force of barriers versus cross-channel synergy International Journal of Information Management Chen, Q., Lu, Y., Gong, Y.Y., Tang, Q. Branded Apps 5 2019 Adoption of mobile applications for identifying tourism destinations by travellers: An integrative approach Journal of Business Economics and Management Kuo, T.-S., Huang, K.-C., Nguyen, P.H. Tourism Apps 6 2019 User acceptance of mobile apps for restaurants: An expanded and extended UTAUT-2 Sustainability Palau-Saumell, R., Forgas-Coll, S., Sánchez-García, J., Robres, E. Tourism Apps 7 2019 Extended expectation-confirmation model to predict continued usage of ODR/ride hailing apps: role of perceived value and self-efficacy Information Technology and Tourism Malik, G., Rao, A.S. Tourism Apps 8 2019 User acceptance of emergency and disaster response mobile application in the Philippines: An investigation based on the unified theory of acceptance and use of technology model International Journal of Enterprise Information Systems Orong, M.Y., Hernandez, A.A. Tourism Apps (Disaster Management) 9 2019 The Joint Impacts of need for Status and Mobile Apps' Social Visibility on Hotel Customers' Behavioral Intentions International Journal of Hospitality and Tourism Administration Fan, A., Wu, L., Mattila, A.S., Yang, W. Tourism Apps 10 2018 Users' acceptance of innovative mobile hotel booking trends: UK vs. PRC Information Technology and Tourism Tao, M., Nawaz, M.Z., Nawaz, S., Butt, A.H., Ahmad, H. Tourism Apps 11 2017 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force of barriers versus cross-channel synergy International Journal of Information Management Chen, Q., Lu, Y., Gong, Y.Y., Tang, Q. Branded Apps 5 2019 Adoption of mobile applications for identifying tourism destinations by travellers: An integrative approach Journal of Business Economics and Management Kuo, T.-S., Huang, K.-C., Nguyen, P.H. Tourism Apps 6 2019 User acceptance of mobile apps for restaurants: An expanded and extended UTAUT-2 Sustainability Palau-Saumell, R., Forgas-Coll, S., Sánchez-García, J., Robres, E. Tourism Apps 7 2019 Extended expectation-confirmation model to predict continued usage of ODR/ride hailing apps: role of perceived value and self-efficacy Information Technology and Tourism Malik, G., Rao, A.S. Tourism Apps 8 2019 User acceptance of emergency and disaster response mobile application in the Philippines: An investigation based on the unified theory of acceptance and use of technology model International Journal of Enterprise Information Systems Orong, M.Y., Hernandez, A.A. Tourism Apps (Disaster Management) 9 2019 The Joint Impacts of need for Status and Mobile Apps' Social Visibility on Hotel Customers' Behavioral Intentions International Journal of Hospitality and Tourism Administration Fan, A., Wu, L., Mattila, A.S., Yang, W. Tourism Apps 10 2018 Users' acceptance of innovative mobile hotel booking trends: UK vs. PRC Information Technology and Tourism Tao, M., Nawaz, M.Z., Nawaz, S., Butt, A.H., Ahmad, H. Tourism Apps 11 2017 ...…”
Section: Resultsmentioning
confidence: 99%
“… 12 2019 The reasons why elderly mobile users adopt ubiquitous mobile social service Computers in Human Behavior Yang, H.-L., Lin, S.-L. 13 2019 Adoption and Use of Mobile Learning in Continuing Professional Development by Health and Human Services Professionals Journal of Continuing Education in the Health Professions Curran, V., Fleet, L., Simmons, K., (…), Garmsiri, M., Wetsch, L. 14 2019 Drivers and outcomes of branded mobile app usage intention Journal of Product and Brand Management Stocchi, L., Michaelidou, N., Micevski, M. 15 2019 A study on factors influencing the adoption of a crowdsourcing mobile application among generation Y and Z in Maldives International Journal of Recent Technology and Engineering Ali, M.M., Maideen, M.B.H. 16 2020 Factors Affecting Consumer Adoption of Mobile Apps in NCR: A Qualitative Study Global Business Review Arora, N., Malik, G., Chawla, D. 17 2019 Viral marketing and purchase intentions of mobile applications users International Journal of Emerging Markets Fard, M.H., Marvi, R. 18 2019 Adoption of mobile applications for identifying tourism destinations by travellers: An integrative approach Journal of Business Economics and Management Kuo, T.-S., Huang, K.-C., Nguyen, P.H. 19 2019 Experience and facilitating conditions as impediments to consumers' new technology adoption International Review of Retail, Distribution and Consumer Research Mahardika, H., Thomas, D., Ewing, M.T., Japutra, A.…”
Section: Methodsmentioning
confidence: 99%
“…By considering its positive valence, Kim et al (2016a), propose to define WOM about App as the "communication of positive evaluation from other users about the target App". In spite of the limited number of studies interested in WOM regarding m-commerce in general and mobile applications in particular (Kim et al, 2014), some research pointed out that customers' intentions to use a mobile application should increase thanks to a positive WOM about this App (Kim, et al, 2016a ;Kuo et al, 2019;San-martin et al, 2016) as consumers tend to check other users' reviews and opinions or ratings regarding mobile apps before downloading them (Racherla et al, 2012). In tourism related products and services which have become available through mobile devices (Chang et al, 2016;Litvin et al, 2018), WOM has been shown to be the information source most frequently used by tourists (Litvin et al, 2008) likely to influence their behaviour and decision making (Harris, 2017).…”
Section: Personal Innovativenessmentioning
confidence: 99%
“…Thus, professionals in various sectors of activity (Hew et al, 2016) rushed to offer their own applications. For instance, in the hospitality and tourism industry, mobile marketing devices are very helpful for both consumers and travel mangers as consumers can collect information about travel, tourism offers; and managers can better present and promote their products and services (Kuo et al, 2019). In fact, hospitality and tourism companies have offered a wide range of mobile applications to customers allowing them to access information, products and services using their mobile devices (Liebana-Cabanillas et al, 2020;Litvin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for lack of success of in-app adoption models can be lack of use of moderators. Among numerous models for adoption of in-app advertisements, very few have included moderators (Adikari, 2017;Kuo, Huang, & Nguyen, 2019). So, there is a need to incorporate moderators.…”
Section: Moderators Relevant To In-app Advertisementmentioning
confidence: 99%